The Oxford Handbook of Economic Forecasting 2012
DOI: 10.1093/oxfordhb/9780195398649.013.0005
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting With DSGE Models

Abstract: This article reviews and illustrates the methodology of forecasting with dynamic stochastic general equilibrium (DSGE) models using Bayesian methods. It discusses an algorithm for estimating the predictive distribution of the observed variables based on draws from the posterior distribution of the DSGE model parameters and simulation of future paths for the variables with the model. The article is organized as follows. Section 2 sketches the new area-wide model (NAWM) and briefly reports on its empirical imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 88 publications
1
46
0
1
Order By: Relevance
“…OSFs are then derived straightforwardly from (2). Suppose the initial forecast origin is m, then the OSFs are :…”
Section: Dsge Model Osfsmentioning
confidence: 99%
“…OSFs are then derived straightforwardly from (2). Suppose the initial forecast origin is m, then the OSFs are :…”
Section: Dsge Model Osfsmentioning
confidence: 99%
“…1 Christoffel, Coenen, and Warne (2010) compare the forecast accuracy of the New Area-Wide Model (NAWM), designed and used by the European Central Bank for macroeconomic forecasts, with Bayesian DSGE-VARs, BVARs and reduced-form models. They find that the DSGE-VAR model outperforms DSGE, NAWM, VAR, and BVAR models in forecasting output.…”
Section: The Forecasting Process: Institutional Backgrounds and Data mentioning
confidence: 99%
“…The main message of our paper is that the ability of DSGE models to forecast real exchange rates, highlighted for the euro area by Adolfson et al (2007b) and Christoffel et al (2011), should not be overplayed as other models that conform with the same principles perform equally well. We have shown that there is indeed not an appreciable difference in the forecasting performance of the DSGE, "AR fixed" and MBVAR models at medium-term horizons.…”
Section: Ecb Working Paper 1905 May 2016 24mentioning
confidence: 96%
“…The MBVAR model is instead more competitive at longer horizons. This highlights that the conclusions of Adolfson et al (2007b) and Christoffel et al (2011) no longer hold when confronted with more competitive benchmarks.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation